2020
DOI: 10.1148/radiol.2020191710
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Lymphatic Vessels in the Lower Extremities: Comparison between Photoacoustic Lymphangiography and Near-Infrared Fluorescence Lymphangiography

Abstract: V ascular and lymphatic vessel networks closely approximate each other in the interstitial environment, and a detailed visualization of these systems is essential to understanding their involvement in both normal physiologic processes and development of pathologic conditions. It is inherently difficult to visualize lymphatic vessels because of their small diameter and because lymph fluid is colorless. Traditionally, lymphatic vessels in the human body are visualized with lymphoscintigraphy, MR lymphangiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…Nevertheless, there is still a long way to go before PAI can be widely applied in brain diseases' clinical diagnosis. Only clinical research on breast cancers and subcutaneous lymph nodes of humans by PAI has been reported (112,113). In the future, the rapid development of nanotechnology and the promotion of PA devices will aid the advancement of photoacoustic molecular imaging, facilitate the preclinical investigation of biological processes in living subjects, and push the PAI modality towards clinical translation.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Nevertheless, there is still a long way to go before PAI can be widely applied in brain diseases' clinical diagnosis. Only clinical research on breast cancers and subcutaneous lymph nodes of humans by PAI has been reported (112,113). In the future, the rapid development of nanotechnology and the promotion of PA devices will aid the advancement of photoacoustic molecular imaging, facilitate the preclinical investigation of biological processes in living subjects, and push the PAI modality towards clinical translation.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…In lymphatic surgery, imaging examinations, including lymphoscintigraphy, indocyanine green lymphography, lymphatic ultrasound, or photoacoustic lymphography, are important. [26][27][28][29][30][31][32][33][34] With these examinations, surgeons can understand individual lymphatic function and determine the appropriate procedure; thus, the reliability and success rates of lymphatic surgery have improved. Similarly, continuing MLB education and training for therapists will ensure adequate lymphedema treatment and increase the effectiveness of therapist techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported the results of the observation of the lymphatic system using photoacoustic imaging. 2 4 Additionally, this device can also record a video as the sensor can be fixed. 5 We obtained the lymphatic flow video of the following case.…”
Section: Sirmentioning
confidence: 99%